Frank, Robert and Sherman Moran, Seattle, ca. 1900 - Unknown
After working on ships for a number of years, the three Moran brothers opened a marine repair shop at Yesler's Wharf in 1882. Over the years, Moran Brothers Company gained an excellent reputation for repairing and building ships. Among other vessels, the company built Yukon River steamboats for the gold rush and and the battleship "Nebraska" for the U.S. Navy. Typed on verso: Moran, Frank, Robert and Sherman. Caption by MOHAI staff. 1 photographic print mounted on cardboard: b&w; 7 1/2 x 9 1/2 in.; torn